Analisis Terhadap Faktor-Faktor yang Mempengaruhi Prestasi Pendidikan Agama Kristen di SDN 001 Malinau Kota - Alung, Septiana (Sekolah Tinggi Teologi Kanaan Nusantara, 2025)
Title: An Analysis of the Factors Influencing the Academic Achievement in Christian Religius Education at SDN 001 Malinau Kota. This thesis seeks to analyze the various factors contributing to the low academic performance of students in the subject of Christian Religus Education (CRE) at SDN 001 Malinau Kota. Based pn data collected during the first semester of the 2024/2025 academic year, it was found that the majority of students in grades IV to VI did not meet the minimum mastery critery (MMC) set by the school, which is a score of 75. This is concerning, considering that CRE is generally perceived as an accessible subject, offering moral and spiritual formation that is essential to students holistic development. The studt employs a desciptive qualitative approach. Data were collected through observation, interviews, and documentation. The findings reveal that several factors contribute to the low academic achievement in CRE, including students limited understanding of the subject matter, a lack of engaging and varied teaching methods, minimal parental support, inadequate educational facilities, and the scarcity of Christian-based reference material for the subject. The study also found that the school has yet to implement specific strategies to address these issues. Hence, there is a need to evaluate the current pedagogical approaches used in teaching CRE and to foster greater involvement of parents in supporting their children’s learning. This research is expected to contribute meaningfully at SDN 001 Malinau Kota.AbstrakJudul dalam penelitian ini adalah “Analisis Terhadap Faktor-Faktor yang Mempengaruhi Prestasi Pendidikan Agama Kristen Di SDN 001 Malinau Kota.” Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi rendahnya pencapaian prestasi belajar peserta didik pada mata pelajaran pendidikan agama Kristen (PAK) di SDN 001 Malinau Kota. Berdasarkan data yang diperoleh pada semester ganjil tahun ajaran 2024/2025, ditemukan bahwa mayoritas siswa kelas IV-VI tidak memenuhi kriteria ketuntasan minimal (KKM) yang sudah ditetapkan oleh pihak sekolah yaitu 75. Padahal, mata pelajaran PAK dipandang relatif mudah dan memiliki muatan pembelajaran yang dapat membentuk karakter serta kerohanian siswa. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil analisis menunjukkan bahwa terdapat beberapa faktor yang mempengaruhi rendahnya prestasi siswa PAK di SDN 001 Malinau Kota, yaitu kurangnya pemahaman siswa terhadap materi PAK, pendekatan pengajaran yang kurang variatif dan masih mnonoton, rendahnya dukungan orang tua, sarana dan prasarana yang kurang memadai, serta keterbatasan buku refrensi PAK. Penelitian ini juga menemukan bahwa belum terdapat strategi khusu dari pihak sekolah dalam mengatasi permasalahan tersebut. Oleh karena itu, dibutuhkan evaluasi terhadap metode pembelajaran Pendidikan Agama Kristen, serta keterlibatan keluarga dalam mendukung pembelajaran siswa. Studi ini diharapkan menjadi kontribusi nyata dalam upaya meningkatkan mutu pendidikan agama di SDN 001 Malinau Kota.